Potential yield gap and agro-economic feasibility of frontline demonstration on mustard (Brassica juncea) in Rajasthan - Meena, D.S.; Tetarwal, J.P.; Ram, Baldev (Annals of Agricultural Research, 2014)
Frontline demonstrations of mustard were organized from 2005-06 to 2010-11 in the Rajasthan to demonstrate the impact of improved production technologies. The selection of farmers was done on the basis of Participatory Rural Appraisal (PRA) action plan. The results indicated that 18.89% yield and 21.91% net return can be obtained by adoption of improved production technology over farmers' practices. The main yield attributing factors were; recommended high yielding varieties, plant geometry, fertilizer application, weed management, plant protection measures and irrigation scheduling responsible for higher yield. Path coefficient showed that above six factors are directly responsible for increasing the yield while factors like poor soil fertility levels, damage by stray cattle and poor technical knowledge are for low yield. Hence' the farmers of the area are advised to adapt the improved technology for higher return and boost up the productivity of mustard in Rajasthan.